Medium, Format, Configuration The Displacements of Film - Turquety, Benoît (Configurations of Film, 2019)
In contrast with media constructed as vast, ontologically homogeneous, non-localized systems, formats show material networks of interoperability and exclusions, inscribed in local specificities, and involving precise conditions for the circulation of images and sounds. Formats, institutionalized as standards, frame the "technical networks" defined by Gilbert Simondon, that unfold technical objects into economically and politically structured webs that cover the world. Media are always formatted and, as such, do not flow: they are displaced.